2015
DOI: 10.1111/aogs.12625
|View full text |Cite
|
Sign up to set email alerts
|

The surgical management of recurrent stress urinary incontinence: a systematic review

Abstract: There is a wide spectrum of surgical interventions reported for secondary or tertiary treatment of SUI. A common characteristic for all recurrent procedures is a lower success rate compared with those reported following primary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 80 publications
(154 reference statements)
0
11
0
1
Order By: Relevance
“…The authors concluded that there was no difference between the retropubic or transobturator approaches to the MUS as the two most studied procedures, while one trial showed no difference between retropubic MUS and colposuspension. A systematic review that allowed pooling of data for small studies, some with as few as five subjects, showed objective cure rates for recurrent SUI treated with colposuspension, MUS, and PVS of 76%, 66%, and 79%, respectively . The success rate for retropubic MUS was higher than for the transobturator approach.…”
Section: Variables Confounding Outcomes Of Surgery For Uimentioning
confidence: 99%
“…The authors concluded that there was no difference between the retropubic or transobturator approaches to the MUS as the two most studied procedures, while one trial showed no difference between retropubic MUS and colposuspension. A systematic review that allowed pooling of data for small studies, some with as few as five subjects, showed objective cure rates for recurrent SUI treated with colposuspension, MUS, and PVS of 76%, 66%, and 79%, respectively . The success rate for retropubic MUS was higher than for the transobturator approach.…”
Section: Variables Confounding Outcomes Of Surgery For Uimentioning
confidence: 99%
“…In a recent review, Nikolopoulos et al [9] suggested that cure rates for recurrent SUI were 68.5% with MUS procedure, 61% with MUS fixation, 76% with Burch colposuspension, 53.8% with adjustable continence therapy and adjustable slings, 38% with bulking agents and 79.3% with pubovaginal slings. Also in this review, success rates of repeat MUS procedures using the transobturator approach appeared lower than in the retropubic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although all surgical treatment options for primary SUI are theoretically suitable for women with failed MUS, the surgeries most commonly performed are Burch colposuspension, laparoscopic 2-team sling procedure, pubovaginal sling, MUS fixation, repeat MUS, injection of urethral bulking agents, adjustable continence therapy and adjustable slings, salvage spiral sling and artificial urinary sphincter [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Uygulanan ikincil cerrahilerin başarı oranı ilk cerrahiden daha düşük seviyededir (15). İngiltere'de ürojinekologların nüks SÜİ'ye yaklaşımlarını araştıran bir çalışmada en sık seçilen cerrahinin %54'lük bir oranla ikinci MUS olduğu ve bunu %14'lük bir oranla mesane boynu enjeksiyonlarının takip ettiği bildirilmiştir (16).…”
Section: Cerrahi Tedaviunclassified